(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The Education Act also set the task of educating the growing generation to be independent-minded. The resolution of this issue also largely depends on the application of interactive teaching techniques. First of all, let’s define the concept of" interactive". the word " interactive "comes from the English word" interact". "Inter "means mutual," Act " means to do, to work. So interactive means being in a state of dialogue (communication) with someone (with a person) in the order of mutual work, activity or conversation. Thus, interactive teaching is, first of all, communicative teaching, in the course of the process, interaction between the teacher and the student is carried out. The essence of interactive teaching is to organize the educational process in such a way that all students, being involved in the process of cognition, have the opportunity to think freely, analyze and reason logically.